A Simple and Scarless Method for Inframammary Fold Correction Using a Barbed Suture. Issue 6 (June 2020) - Tomita, Koichi; Taminato, Mifue; Nomori, Michiko; Maeda, Daisuke; Seike, Shien; Tashima, Hiroki; Yano, Kenji; Kubo, Tateki
Abstract : Background: In the typical procedure for secondary correction of the inframammary fold (IMF) following breast reconstruction, a large incision is often required, and this increases surgical invasiveness. The "drawstring method" is a simple procedure for recreating a smooth IMF. We modified the drawstring method and developed an essentially scarless method for IMF correction from small stab incisions. Methods: Patients at our hospital who presented with IMF ptosis or loss of definition after breast reconstruction and required IMF correction, as well as those who requested IMF recreation for the contralateral breast, during the period spanning May 2016 to June 2019 were considered for this study. We collected and analyzed demographic data, as well as complications and postoperative outcomes. Results: The new method was performed on 20 patients, with the following breakdown: IMF recreation after breast reconstruction with a deep inferior epigastric artery perforator flap (11 patients), IMF recreation after breast reconstruction with a breast implant (2 patients), IMF recreation after breast reconstruction with fat graft (5 patients), and IMF recreation for the contralateral breast (2 patients). Overcorrection of the IMF stabilized by 2–3 months postoperatively, resulting in a smooth and well-defined IMF. For non–breast implant cases, the implant volume increased at the lower pole. Slack in the suture was observed in only 2 patients of the deep inferior epigastric artery perforator group and in 1 patient of the breast implant group after 6 months postoperatively. Conclusions: Our new method allows for the recreation of an essentially scarless, smooth, and well-defined IMF. IMF definition can be adjusted by altering the depth of the barbed suture. Since this method can be performed under local anesthesia, it offers the benefits of reducing medical costs and physical burden on patients.